MYORG-related disease is associated with central pontine calcifications and atypical parkinsonism. (April 2020) - Chelban, Viorica; Carecchio, Miryam; Rea, Gillian; Bowirrat, Abdalla; Kirmani, Salman; Magistrelli, Luca; Efthymiou, Stephanie; Schottlaender, Lucia; Vandrovcova, Jana; Salpietro, Vincenzo; Salsano, Ettore; Pareyson, Davide; et al.
Abstract : Objective: To identify the phenotypic, neuroimaging, and genotype-phenotype expression of MYORG mutations. Methods: Using next-generation sequencing, we screened 86 patients with primary familial brain calcification (PFBC) from 60 families with autosomal recessive or absent family history that were negative for mutations in SLC20A2, PDGFRB, PDGBB, and XPR1 . In-depth phenotyping and neuroimaging investigations were performed in all cases reported here. Results: We identified 12 distinct deleterious MYORG variants in 7 of the 60 families with PFBC. Overall, biallelic MYORG mutations accounted for 11.6% of PFBC families in our cohort. A heterogeneous phenotypic expression was identified within and between families with a median age at onset of 56.4 years, a variable combination of parkinsonism, cerebellar signs, and cognitive decline. Psychiatric disturbances were not a prominent feature. Cognitive assessment showed impaired cognitive function in 62.5% of cases. Parkinsonism associated with vertical nuclear gaze palsy was the initial clinical presentation in 1/3 of cases and was associated with central pontine calcifications. Cerebral cortical atrophy was present in 37% of cases. Conclusions: This large, multicentric study shows that biallelic MYORG mutations represent a significant proportion of autosomal recessive PFBC. We recommend screening MYORG mutations in all patients with primary brain calcifications and autosomal recessive or negative family history, especially when presenting clinically as atypical parkinsonism and with pontine calcification on brain CT.